Efficiency assessment of operational and maintenance techniques to optimize sewer gas amount - Othman, Faridah; Mortezania, Shahram (Academic Journals, 2010)
The study presented here is a preliminary effort to compare sewer operational and maintenance techniques to assess their efficiency in optimizing the amount of gases (that is, H2S and O-2) in sewage collection networks in Mashhad-Iran. Field tests were carried out using high-pressure water jet cleaning (HPWJC), portable blower ventilation (PBV), and water flushing (WF) techniques at specific intervals. The outcomes revealed that proactive maintenance is useful to optimize the range of gases in sewers; that is, H2S < 1 ppm and O-2 > 20%. The results obtained from performing the designed methods showed that test No. 2 (2 times/30 days), test No. 6 (3 times/30 days), and test No. 8 (2 times/30 days) for HPWJC, PBV, and WF techniques respectively are efficient enough to satisfy H2S and O-2 ranges at headspace of the networks. However, among these, WF technique with the application of 2 times/30 days was nominated as the most effective method due to its safety to the network and its performance in leading the H2S amount to less than 1 ppm and O-2 percentage by more than 20%.